2015
DOI: 10.1021/tx5004563
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctyl Iodide Stimulates Steroidogenesis in H295R Cells via a Cyclic Adenosine Monophosphate Signaling Pathway

Abstract: Perfluorinated iodine alkanes (PFIs) are used widely in the organic fluorine industry. Increased production of PFIs has caused environmental health concerns. To evaluate the potential endocrine-disrupting effect of PFIs, we investigated the effects of perfluorooctyl iodide (PFOI) on steroidogenesis in human adrenocortical carcinoma cells (H295R). Levels of aldosterone, cortisol, 17β-estradiol, and testosterone were measured in H295R culture medium upon treatment with perfluorooctanoic acid (PFOA) and PFIs. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…In steroidogenesis (SI Figure S7), cholesterol was first transferred to the inner mitochondrial membrane by StAR, converted to progesterone by CYP11A1, and subsequently metabolized through multistep process to aldosterone, cortisol, T and E 2 , respectively, under the regulation of diverse enzymes, including 3βHSD, CYP21, CYP11B1, CYP11B2, CYP17, 17βHSD, and CYP19 etc. 24 As demonstrated previously, 38 the significant up-regulation of target gene transcriptional levels induced by 10 μM forskolin (SI Figure S6), was consistent with increased steroid hormone secretion (SI Figure S5), showing the crucial correlation between the expression of key steroidogenic genes and hormone levels. To understand how SPAs disturbed steroidogenesis, BHA was selected as a representative compound for the study of its function on these target genes.…”
Section: Discussionsupporting
confidence: 80%
“…In steroidogenesis (SI Figure S7), cholesterol was first transferred to the inner mitochondrial membrane by StAR, converted to progesterone by CYP11A1, and subsequently metabolized through multistep process to aldosterone, cortisol, T and E 2 , respectively, under the regulation of diverse enzymes, including 3βHSD, CYP21, CYP11B1, CYP11B2, CYP17, 17βHSD, and CYP19 etc. 24 As demonstrated previously, 38 the significant up-regulation of target gene transcriptional levels induced by 10 μM forskolin (SI Figure S6), was consistent with increased steroid hormone secretion (SI Figure S5), showing the crucial correlation between the expression of key steroidogenic genes and hormone levels. To understand how SPAs disturbed steroidogenesis, BHA was selected as a representative compound for the study of its function on these target genes.…”
Section: Discussionsupporting
confidence: 80%
“…PFAS are also known to have weak oestrogenic activity and, as with other weak oestrogens, exposure to a combination of E2, and these compounds produced anti-estrogenic effects ( Liu et al , 2007 ). Studies have reported contradictory results using in vitro screening systems to assay for hormone activity by ER- or AR-mediated transactivation in the human breast adenocarcinoma cell lines MCF-7 and MVLN ( Maras et al , 2006 ; Wang et al , 2012 ; Kjeldsen and Bonefeld-Jørgensen, 2013 ; Behr et al , 2018 ), human adrenal carcinoma cell H295R ( Du et al , 2013a ; 2013b ; Wang et al , 2015 ; Behr et al , 2018 ) and human placental choriocarcinoma cell JEG-3 ( Gorrochategui et al , 2014 ), as well as in in vivo testing ( Biegel et al , 1995 ; Du et al , 2013a ; Yao et al , 2014 ). It remains unclear whether PFAS affect oestrogen or androgen receptor signalling at concentrations relevant to human exposure.…”
Section: Mechanistic Evidence For Ovarian Toxicity Of Pfasmentioning
confidence: 99%
“…The steroidogenic acute regulatory protein (StAR) was responsible for transferring cholesterol from the outer mitochondrial membrane to the inner one, which hosts the cytochrome P450 side-chain cleavage (P450 SCC) enzyme 30 . P450scc converts cholesterol to pregnenolone, which is subsequently transported to the smooth endoplasmic reticulum, where it is converted to testosterone by CYP17, CYP21, 3-hydroxysteroid dehydrogenase (3-HSD), and 17-hydroxysteroid dehydrogenase (17-HSD) 31 35 . In the testes, the 17-HSD enzyme is almost expressed and is needed for testosterone biosynthesis 36 .…”
Section: Introductionmentioning
confidence: 99%